1989
DOI: 10.1002/em.2850130107
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxygen free radicals in the induction of sister chromatid exchanges by cigarette smoke

Abstract: Cigarette smoke has been reported to contain free radicals and free radical generators in both the gas and particulate phases. Studies in our laboratory have shown that both cigarette smoke condensate (CSC) and smoke bubbled through phosphate buffered saline solution (smoke-PBS) increased sister chromatid exchanges (SCE) in Chinese hamster ovary cells in a dose-dependent manner. Since oxygen free radicals have been shown to cause SCEs and other chromosomal damage, we investigated the role of these radicals in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…This in vivo induction may be primarily caused by pathways not involving free radicals or oxidation reactions. This possibility is supported by in vitro experiments on SCE induction by cigarette smoke (Lee et al, 1989). If so, this would explain the absence of an effect of p-carotene without precluding its protective potential in other DNAdamaging pathways.…”
Section: Discussionmentioning
confidence: 92%
“…This in vivo induction may be primarily caused by pathways not involving free radicals or oxidation reactions. This possibility is supported by in vitro experiments on SCE induction by cigarette smoke (Lee et al, 1989). If so, this would explain the absence of an effect of p-carotene without precluding its protective potential in other DNAdamaging pathways.…”
Section: Discussionmentioning
confidence: 92%
“…Reactive oxyradicals are known mediators of the indirect effect of ionizing radiation. There is considerable evidence, including ours, that ROS are involved in the genotoxicity of arsenite (22,53), asbestos (38,54), and cigarette smoke condensate (55). With the use of Chinese hamster ovary cells and an x-ray-hypersensitive, DNA repair-deficient mutant, XRS-5, Wang and Huang showed that arsenite induced a dosedependent increase in micronuclei that was blocked by exogenous catalase (41).…”
Section: Discussionmentioning
confidence: 98%
“…The effects of cigarette smoke on oxidative stress are well known as are the effects of smoke on cellular apoptosis [59][61]. Increased lipid peroxidation, reduced glutathione contents, increased catalase activity, decreased SOD activity, cytoplasmic retractions and fewer intercellular junctions were observed in granulosa cells exposed to Cd [62], [63], a heavy metal compound in cigarette smoke.…”
Section: Discussionmentioning
confidence: 99%